P81 The association between air pollution and acute hospital admissions in dublin 2007–2016. (3rd September 2019) - Robinson, M; Kelly, G; O'Reilly, E
Abstract : Background: Outdoor air pollution has a significant impact on human health and has been declared a 'public health emergency' by the World Health Organisation. An estimated 14, 400 years of life are lost annually in Ireland due to 1200 premature deaths caused by air pollution. Cardiovascular disease and stroke are the commonest causes of premature death, followed by respiratory disease. Numerous studies worldwide have described the association between air pollution and acute illness, however few studies have been conducted in Ireland to date. This study estimates the association between changes in mean daily air pollutant levels and daily acute hospital admissions in Dublin. Methods: Mean 24-hour levels of fine particulate matter (PM2.5 ), coarse particulate matter (PM10 ), and pollutant gases were calculated for the central Dublin area as a whole, using data from EPA monitors between 2007 and 2016. Daily total acute hospital admissions for respiratory and cardiovascular/cerebrovascular conditions were obtained from Healthcare Pricing Office records, for hospitals within the Dublin area, over the same period. Univariate analyses were performed, to investigate the association between individual pollutants and admissions, followed by analyses that mutually adjusted for several pollutants, with a lag of up to 2 days, to further describe the associations observed. Meteorological variables were controlled for in the model. Results: Univariate analysis revealed carbon monoxide as the strongest predictor of respiratory admissions. Multivariate analysis also identified sulphur dioxide as a strong predictor of respiratory admissions and PM2.5 and nitrogen dioxide as the strongest predictors of cardiovascular admissions. Conclusion: This study describes the extent of the impact of air pollution on hospital admissions and presents models for predicting future admissions with varying levels of pollution. The findings may inform policies to reduce urban air pollution, to develop early warning systems for the public and to improve the preparedness of hospital emergency departments on days of poor air quality.